The Oral Microbiota: Community Composition, Influencing Factors, Pathogenesis, and Interventions - Li, Xinyi; Liu, Yanmei; Yang, Xingyou; Li, Chengwen; Song, Zhangyong (Frontiers in Microbiology, 2022)
The human oral cavity provides a habitat for oral microbial communities. The complexity of its anatomical structure, its connectivity to the outside, and its moist environment contribute to the complexity and ecological site specificity of the microbiome colonized therein. Complex endogenous and exogenous factors affect the occurrence and development of the oral microbiota, and maintain it in a dynamic balance. The dysbiotic state, in which the microbial composition is altered and polymicrobial biofilms form, can lead to oral and even systemic diseases. In this review, we discuss the current research on the composition of the oral microbiota, the factors influencing it, and its relationships with common oral diseases. We focus on the specificity of the microbiota at different niches in the oral cavity, the communities of the oral microbiome, the mycobiome, and the virome within oral biofilms, and interventions targeting oral pathogens associated with disease. With these data, we aim to extend our understanding of oral microorganisms and provide new ideas for the clinical management of infectious oral diseases.